Flipping Activity and Subsequent Aftermarket Trading in Malaysian IPOs - Ruzita Abdul Rahim; Ros Zam Zam Sapian; Othman Yong; Noor Azryani Auzairy (Asian Academy of Management Journal of Accounting and Finance, 2013)
This paper examines the aftermarket trading volume following an initial public offering (IPO) in a sample of 243 IPOs listed on Bursa Malaysia between June 2003 and June 2008. Specifically, this study investigates the degree of flipping activity and its relationship with six ex-ante variables including IPO initial returns. Consistent with previous studies, the result of the cross-sectional multiple regression reveals a significantly strong positive relationship between initial returns and flipping activity for IPOs. Initial returns also seem to influence the subsequent week’s trading volume, but the influence is completely absorbed by flipping activity. The results also show that both institutional investor participation and offer size have significant influences on flipping activity. The results of this study imply that the Malaysian IPO market experiences active flipping activity that, in turn, has a significant role in predicting the subsequent trading activity.